A study on factors of influencing consumer purchase intention towards multinational natural personal care product in Klang valley - Mak, Hui Yi; Wong, Mei Cheng (2019)
This study aimed to examine the factors of influencing consumer purchase intention towards multinational personal care products in Klang Valley. Consumer purchase intention always be developed and affected by different reasons and factors that makes the consumer have the intended to purchase multinational natural personal care products and what can be improve in the future. In this research study, the independent variables are environment consciousness, subjective norms, past experiences and health consciousness will be considered as the determinants of the factors that influencing the dependent variable which is purchase intention. Our target population will be Gen Y who aged between 24-38 years old. We conducted a total of 200 sets of the questionnaire to our target population by using the convenience sampling technique. In order to assess the reliability, the Cronbach’s Alpha will be used to measure the reliability test. Moreover, the data collected will be analyzed by using the Multiple Regression Analysis. Based on the results of the research study, the respondents agree that environment consciousness, subjective norms and health consciousness is an important factor influencing consumer purchase intention while environment consciousness has the greater impact to consumer purchase intention. The results of this research study suggest that consumer who had greater environment consciousness will have greater purchase intention towards multinational natural personal care products.